A prospective study on MRI findings and prognostic factors in athletes with MTSS. Issue 1 (20th April 2012) - Moen, M. H.; Schmikli, S. L.; Weir, A.; Steeneken, V.; Stapper, G.; de, R.; Tol, J. L.; Backx, F. J. G.
<x xml:space="preserve">Abstract</x> In medial tibial stress syndrome (MTSS) bone marrow and periosteal edema of the tibia on the magnetic resonance imaging (MRI) is frequently reported. The relationship between these MRI findings and recovery has not been previously studied. This prospective study describes MRI findings of 52 athletes with MTSS. Baseline characteristics were recorded and recovery was related to these parameters and MRI findings to examine for prognostic factors. Results showed that 43.5% of the symptomatic legs showed bone marrow or periosteal edema. Absence of periosteal and bone marrow edema on MRI was associated with longer recovery (P = 0.033 and P = 0.013). A clinical scoring system for sports activity (SARS score) was significantly higher in the presence of bone marrow edema (P = 0.027). When clinical scoring systems (SARS score and the Lower Extremity Functional Scale) were combined in a model, time to recovery could be predicted substantially (explaining 54% of variance, P = 0.006). In conclusion, in athletes with MTSS, bone marrow or periosteal edema is seen on MRI in 43, 5% of the symptomatic legs. Furthermore, periosteal and bone marrow edema on MRI and clinical scoring systems are prognostic factors. Future studies should focus on MRI findings in symptomatic MTSS and compare these with a matched control group.